130k views
1 vote
What did they say about the man who died from drinking shellac?

2 Answers

2 votes
He had a lovely finish
User Indubitablee
by
6.8k points
5 votes

Answer is:


He had a lovely finish.

_______________________________

Answer 1:


(x + 4)(x + 2)


Multiplying the binomials by distributing them,

we get;


= x² + 2x + 4x + 8


Adding up the like terms.


= x² + 6x + 8


The answer refers to the letter choice H.

_______________________________

Answer 2:


(x + 7)(x + 1)


Multiplying the binomials by distributing them,

we get;

= x² + 7x + 1x + 7


Adding up the like terms.


= x² + 8x + 7


The answer refers to the letter choice E.

_______________________________

Answer 3:


(x - 6)(x - 3)


Multiplying the binomials by distributing them,

we get;


= x² - 3x - 6x + 18

Adding up the like terms.


= x² - 9x + 18


The answer refers to the letter choice H.

_______________________________

Answer 4:


(x + 8)(x - 2)


Multiplying the binomials by distributing them,

we get;

= x² - 2x + 8x - 16


Adding up the like terms.


= x² + 6x - 16


The answer refers to the letter choice A.

_______________________________

Answer 5:


(x - 7)(x + 4)


Multiplying the binomials by distributing them,

we get;


= x² + 4x - 7x - 28


Adding up the like terms.


= x² - 3x - 28


The answer refers to the letter choice D.

_______________________________

Answer 6:


(x - 2)(x - 9)


Multiplying the binomials by distributing them,

we get;


= x² - 9x - 2x + 18


Adding up the like terms.


= x² - 11x + 18


The answer refers to the letter choice A.

_______________________________

Answer 7:

(2u + 4)(u + 1)


Multiplying the binomials by distributing them,

we get;


= 2u² + 2u + 4u + 4


Adding up the like terms.


= 2u² + 6u + 4


The answer refers to the letter choice L.

_______________________________

Answer 8:


(3u + 7)(u - 3)


Multiplying the binomials by distributing them,

we get;


= 3u² - 9u + 7u -21

Adding up the like terms.


= 3u² - 2u - 21


The answer refers to the letter choice O.

_______________________________

Answer 9:


(4u - 2)(5u - 1)


Multiplying the binomials by distributing them,

we get;


= 20u² - 4u - 10u + 2


Adding up the like terms.


= 20u² - 14u + 2


The answer refers to the letter choice V.

_______________________________

Answer 10:


(2u + 1)(9u - 5)


Multiplying the binomials by distributing them,

we get;


= 18u² - 10u + 9u - 5


Adding up the like terms.


= 18u² - u - 5


The answer refers to the letter choice E.

_______________________________

Answer 11:


(7u - 4)(3u + 6)


Multiplying the binomials by distributing them,

we get;


= 21u² + 42u - 12u - 24


Adding up the like terms.


= 21u² + 30u - 24


The answer refers to the letter choice L.

_______________________________

Answer 12:


(5u - 8)(4u - 4)


Multiplying the binomials by distributing them,

we get;


= 20u² - 20u - 32u + 32


Adding up the like terms.


= 20u² - 52u + 32


The answer refers to the letter choice Y.

_______________________________

Answer 13:


(2x + y)(x + 3y)


Multiplying the binomials by distributing them,

we get;


= 2x² + 6xy + 1xy + 3y²


Adding up the like terms.


= 2x² + 7xy + 3y²

The answer refers to the letter choice F.

_______________________________

Answer 14:


(3x - y)(8x - y)


Multiplying the binomials by distributing them,

we get;

= 24x² - 3xy - 8xy + y²


Adding up the like terms.


= 24x² - 11xy + y²

The answer refers to the letter choice I.

_______________________________

Answer 15:


(2x + y)(4x - 3y)


Multiplying the binomials by distributing them,

we get;

= 8x² - 6xy + 4xy - 3y²


Adding up the like terms.


= 8x² - 2xy - 3y²

The answer refers to the letter choice N.

_______________________________

Answer 16:


(5x - 2y)(3x + 4y)


Multiplying the binomials by distributing them,

we get;

= 15x² + 20xy - 6xy - 8y²


Adding up the like terms.


= 15x² + 14xy - 8y²

The answer refers to the letter choice I.

_______________________________

Answer 17:


(7x + 3y)(x + 2y)


Multiplying the binomials by distributing them,

we get;

= 7x² + 14xy + 3xy + 6y²


Adding up the like terms.


= 7x² + 17xy + 6y²

The answer refers to the letter choice S.

_______________________________

Answer 18:


(6x + 6y)(2x - 4y)


Multiplying the binomials by distributing them,

we get;

= 12x² - 24xy + 12xy - 24y²


Adding up the like terms.


= 12x² - 12xy - 24y²

The answer refers to the letter choice H.

_______________________________



What did they say about the man who died from drinking shellac?-example-1
What did they say about the man who died from drinking shellac?-example-2
User JoCuTo
by
6.2k points